The Guidelines of Islamic State in Cultural Management Emphasizing the views of Morteza Motahhari - Ali Baqi Nasrabadi (‫سیاست متعالیه‏, 2021)
The purpose of the present study is to recognize the guidelines of the Islamic state in cultural management from the perspective of the martyred professor Motahhari. The main question of the study is what is the main responsibility of the Islamic state for the cultural management in society. The method of study is descriptive analysis and it relies on the hypothesis that the Islamic state has a main role in the cultural management. The results of the study show that Shahid Motahhari with reference to the Islamic ideology proves that the Islamic state in the realm of cultural management applies two key guidelines. The religious state has two main responsibilities, one is to recognize its audience, and another is to pave the way for improving culture in society.